Application of furanone compounds for the modulation of biofilm formation in common wound pathogens. Issue Volume 1(2019)Issue A (8th March 2019) - Proctor, Chris; Ternan, Nigel; McCarron, Paul
Abstract : Chronic wounds are a significant issue in healthcare, presenting a considerable economic burden to the NHS and a serious health risk to patients. The majority of non-healing wounds have been shown to contain a biofilm which prolongs the inflammatory stage of wound healing and significantly delays wound healing. This often causes a normal wound to progress and become chronic, presenting further problems for patients including increased risk of secondary infection, further deterioration of the wound and an increase in treatment intensity. This project aims to assess the efficacy of several compounds in modulating the formation of biofilms in a number of clinically relevant pathogens when used at sub-inhibitory concentrations. The organisms used in this project include Pseudomonas aeruginosa and Staphylococcus aureus. We aim to test the efficacy of three plant derived compounds including 4-hydroxy-2, 5-dimethyl-3(2 h) furanone (HDMF), 2-methyltetrahydrofuran-3-one (MTHF) and l-ascorbic acid. Future work will characterise the efficacy of these compounds when delivered to a biofilm from a hydrogel based delivery system. At sub-inhibitory concentrations in pure solution, candidate molecules tested to date showed no ability to reduce biofilm formation. Indeed, treatment with HDMF resulted in greater production of biofilm in P. aeruginosa and treatment with all compounds showed no difference in biofilm formation by S. aureus . To characterise the impact of hydrogel based delivery on compound efficacy all candidate molecules were loaded into a hydrogel and shown to be effectively released from it. Experiments to characterise the modulatory potential of these compounds when released from a hydrogel are currently underway.